Chronic prostatitis and related psychological problems. Which came first: The chicken or the egg? A systematic review (Archivio Italiano di Urologia e Andrologia, 2023)
Introduction/Aim: A spectrum of psychological problems is commonly found in CP/CPPS patients, though it is not yet clear whether, a priori, psychological dysfunctions are the cause of these pain syndromes, or whether these pain conditions are themselves causing psychological disturbances. In this article we present the current perspective on the impact of psychological problems in chronic prostatitis syndromes and we discuss the implications thereof from a clinical perspective.Materials and Methods: A database and a manual search were conducted in the MEDLINE database of the National Library of Medicine, EMBASE, and other libraries using the key words “prostatitis syndromes”, “chronic bacterial prostatitis”, “chronic pelvic pain”, in various combinations with the terms “psychological issues”, “depression” “anxiety”, “stress”, “unhappiness”, “cognitive status” and “personality”. Two independent reviewers performed data extraction. We included clinical studies with available information on chronic prostatitis and related psychological conditions. We considered full-text written papers. We excluded reviews and case reports. In order to reduce the risk of bias we analyzed only studies including patients with confirmed CBP or CP/CPPS. Bibliographic information in the selected publications was checked for relevant records not included in the initial search.Results: Database search allowed us to retrieve 638 studies to which we added to 16 additional studies retrieved by hand-searching. After screening, 34 relevant papers were identified for thorough review. Most studies included patients with chronic pelvic pain and prostatitis-like symptoms, whereas a smaller number of studies included patients with methodologically con- firmed CP/CPPS including studies with a microbiologically confirmed diagnosis of CBP. The psychosocial factors examined in the selected studies include pain, catastrophizing, stress, personality factors and social aspects. Comorbid psychiatric disorders evidenced in the studies included depression, anxiety and trauma-related disorders, somatization disorders, and substance abuse. Some studies investigated the association of pain with each individual psychological disturbance, while others examined the impact of pain in association with the overall quality of life. Sample size, study design and diagnostic measures varied among studies.Conclusions: Despite limitations and variations in sample size, study design and diagnostic measures in all included studies, a relation between chronic prostatitis and psychological problems is a consistent finding. The existing evidence does not permit to definitely conclude whether psychological problems are a risk factor for CP/CPPS or whether they represent an array of symptoms that are associated with the exacerbation of this disease.
Keywords: Prostatitis syndromes; Chronic bacterial prostatitis; Chronic pelvic pain; Psychological issues; Depression; Anxiety; Stress; Unhappiness; Cognitive status; Personality